Broaching force prediction of nickel-based superalloy based on material parameter identification. (July 2022) - Ma, Yongjie; Cheng, Guang; Jiang, Erbiao
The broaching process of the nickel-based superalloy determines the aero-engine turbine disc mortises performance; thus, the broaching force should be analyzed principally. The aim of the study is to reveal the material constitutive law for the nickel-based GH4169 alloy broaching force prediction. However, the GH4169 material constitutive model may just be verified by the hot compression tests at the limited high-temperature conditions. The residual stress-based finite element updating (FEU) inverse method was used to optimize the GH4169 material parameters. And the finite element (FE) model for the whole multi-stage processing of the turbine disc billet was simulated with high efficiency and accuracy, where the wide forming temperature range would be the critical factor for the consequent broaching analysis. The cutting conditions were tested to measure the residual stresses in the multi-stage formed GH4169 alloy disc billet by the layer removal method. The objective function (OF) designed with the experimental-numerical residual stresses were optimized successfully. The GH4169 alloy broaching force predicted with the identified thermo-mechanical material constitutive model in this study was satisfied with the validation test results, and the influence of cutting parameters on the broaching force distribution design could be effectively controlled, which could guarantee the high dimensional accuracy and the excellent reliability of the aero-engine turbine disc.